A multi-component tailored intervention in family childcare homes improves diet quality and sedentary behavior of preschool children compared to an attention control: results from the Healthy Start-Comienzos Sanos cluster randomized trial - Kim M. Gans; Alison Tovar; Augustine Kang; Dianne Stanton Ward; Kristen Cooksey Stowers; Tayla von Ash; Laura Dionne; George Dennis Papandonatos; Noereem Mena; Qianxia Jiang; Patricia Markham Risica (BMC, 2022)
Abstract Background Childcare settings are important environments for influencing child eating and physical activity (PA). Family childcare homes (FCCH) care for many children of low-income and diverse racial/ethnic backgrounds who are at greater risk for poor diet quality, low PA, and obesity, but few interventions have targeted this setting. The aim of this study was to assess the efficacy of a multicomponent intervention conducted in FCCH on the diet quality and PA of 2-5 year old children in their care. Trial design Cluster randomized trial. Methods The cluster-randomized trial, Healthy Start/Comienzos Sanos (2015-2019) evaluated an 8-month nutrition and PA intervention that included four components: (1) monthly telephone calls from a support coach using brief motivational interviewing, (2) tailored reports, newsletters and videos, (3) group support meetings, and (4) active play toys. After completing baseline measurement, FCCH were randomized into intervention or comparison groups in matched pairs. Both groups received the same intervention components but on different topics (intervention: nutrition/PA vs. comparison: reading readiness/literacy). Evaluation staff were blinded to group assignment. Child primary outcome measures collected at baseline and 8-months included: 1) Healthy Eating Index (HEI-2015) scores calculated from diet observation, and 2) accelerometer measurement of PA. Process measures were collected from field data and provider surveys. Generalized Estimating Equation Models assessed changes in HEI-2015 scores and PA over time by experimental condition. Results Ethnically diverse FCCH providers (n = 119) and 2-to-5-year-old children in their care (n = 377) were included in the final analysis. Process evaluation showed high participation in all intervention components except for group meetings. Compared to children in comparison group FCCH, children in intervention FCCH increased total HEI-2015 scores by 7.2 points (p < .001) including improvement in component scores for vegetables (0.84 points, p = .025) and added sugar (0.94 points, p = .025). For PA, compared to children in the comparison group, children in intervention FCCH decreased sedentary time by 5.7% (p = .021). Conclusions The multicomponent Healthy Start intervention was effective in improving diet quality and sedentary behavior of children in FCCH, which demonstrates the promise of obesity prevention interventions in this setting. Future research could include enhancing the Healthy Start intervention to strengthen the PA component, considering virtual peer support, and determining how to best translate and disseminate the intervention into FCCH nationally. Trial registration National Institutes of Health, NCT02452645 . Registered 5 May 2015.